Advanced cancer patients' attitudes towards, and experiences with, screening for somatic mutations in tumours: a qualitative study. (11th October 2016) - Liang, R.; Meiser, B.; Smith, S.; Kasparian, N.A.; Lewis, C.R.; Chin, M.; Long, G.V.; Ward, R.; Menzies, A.M.; Harris‐Wai, J.N.; Kaur, R.
Abstract : Somatic mutations in key oncogenes in non‐small cell lung cancer (NSCLC) and melanoma are important determinants of tumour sensitivity to targeted therapies. Molecular screening for these predictive biomarkers is routinely used to inform treatment decisions; however, little is known about how best to communicate testing and results to patients. This qualitative study aimed to explore advanced cancer patients' attitudes and experiences regarding somatic tumour screening to identify their information and support needs. Sixteen NSCLC and eight melanoma patients who had undergone screening participated in a semi‐structured face‐to‐face or telephone interview exploring their understanding, views, preferences and needs regarding screening. Interviews were audiotaped, transcribed and analysed for thematic patterns. Participants expressed positive views and unequivocal acceptance of screening, and understood its role in guiding treatment selection. They preferred to receive information verbally through simple, non‐technical language from their oncologist with additional take‐home materials. Patients were interested in learning about their test results, but wanted discussion to be focused on practical matters relevant to treatment. While receiving their screening results was not considered burdensome, information overload and cancer‐related distress were identified as barriers to test comprehension. Patients may benefit from information and decision‐related tools to better understand genomic information and adequately support psychosocial outcomes.